Plumage development and growth of wild Surf Scoter Melanitta perspicillata ducklings - Lesage, Louis; Reed, Austin; Savard, Jean-Pierre L (Wildfowl, 1996)
The plumage development and growth of wild Surf Scoter ducklings were studied in a 640 ha boreal forest lake in Quebec by observing and photographing free-ranging individuals and by examining live-caught birds. During their first three to five days, Surf Scoter ducklings were uniformly dark with few distinctive markings. Subsequently, the appearance of a pale-coloured cheek patch added some contrast to their pattern but they remained generally undistinctive through to fledging, at which time they were quite similar in size, appearance and colouration to the female parent. Subtle differences in the shape, size and colouration of the cheek patch, and neck posture (head held close to body or erect), were useful clues to distinguish age classes in the field. Body mass increased from about 44 to 817 g during the 55-day period between hatching and fledging, whereas head length increased from 41 to 97 mm. Few differences in plumage development or growth pattern were noted from studies of other duck species.